Nitrogênio de resíduos de culturas de verão em frações físicas da matéria orgânica de dois solos de terras baixas - Pollet, Carolina Schultz (2018)
Rio Grande do Sul has about 20% of its total area of soils with hydromorphic characteristics, denominated lowlands suitable for rice cultivation (Oryza sativa) irrigated by flooding. In order to mitigate damage caused by rice monoculture, new crops such as sorghum (Sorghum bicolor) and soybean (Glycine max) have been cultivated in these areas. Considering different qualities of cultural residues, a change in the availability of nitrogen (N) present in soil organic matter (SOM) is expected. The aim of this study was to understand the influence of cultural residues of rice, soybean and sorghum on the dynamics of N in different physical fractions of the MOS in two soils of lowlands with different textures, using the technique of isotopic marking of 15N. Simulating an agricultural year, an incubation of the cultural residues of rice, soybean and sorghum enriched with 15N isotope in the soils Planossolo Hidromórfico Eutrófico gleissólico and Planossolo Hidromórfico Eutrófico arênico during 360 days, and at 180 days thereafter the soil was flooded. The remaining N of the plant residues was quantified at 30,180 and 360 days after the beginning of the incubation. The N destination from the residues in the soils was evaluated in the whole soil and after the physical fractionation of the MOS based on the particle size (> 250μm, 250-53μm and <53μm). Higher amounts of 15N in the soil in fractions <53 μm for all incubation periods were quantified. In the treatments with cultural residues of rice and at the end of the incubation period, the largest additions of 15N to the soil were observed. The results indicate that rice cultural residues contribute more effectively to the addition of N in the SOM of hydromorphic soils than soybean and sorghum residues after a one year cycle of the addition of residues. The soil with greater amount of clay was quantified a greater quantity of 15N in the physical fractions due to the greater protection of the SOM by silt and clay. Soil flooding after the decomposition of soybean and sorghum residues causes a loss of N added to the soil by the residues. These losses of N should be considered in nitrogen fertilization for the following crops.